Assessing the detection and interaction of Lawsonia intracellularis and porcine circovirus 2 in low and high-performance wean-to-finish pig groups in different porcine reproductive and respiratory syndrome virus detection scenarios - Cezar, Guilherme; Leite, Fernando L.; Fano, Eduardo; Phillips, Reid; Waddell, John; Dion, Kate; Magalhães, Edison; Trevisan, Giovani; Silva, Gustavo; Linhares, Daniel C. (Frontiers in Veterinary Science, 2025)
IntroductionEffective disease management strategies are essential for achieving optimal pig performance, ensuring high-quality animal health and welfare, and maintaining the economic viability of swine systems. Thus, understanding factors that lead to more or less severe disease are critically important. Porcine circovirus type 2 (PCV2) and Lawsonia intracellularis (L. intracellularis) are endemic pathogens in the U.S., affecting herds with varying degrees of subclinical and clinical disease and impact on performance. While these are common pathogens, their interaction with PRRSV and performance has seldom been investigated. This study investigated the detection dynamics of L. intracellularis, PRRSV, and PCV2, and their association with productivity impacts in wean-to-finish groups within a Midwest U.S. production system.MethodologyThis observational field study involved batches of growing pigs from PRRSV-stable or PRRSV-negative sow farms. Oral fluids were collected longitudinally from weaning until market age, and tested using quantitative PCR for each of the aforementioned pathogens. The study included 36 batches with a total of 46,446 growing pigs, resulting in 4,000 oral fluid samples. Then, batches were categorized based on key performance indicators (mortality and average daily gain), PRRSV detection timing and total genomic copies of each pathogen.ResultsNineteen groups were characterized as high-performance and seventeen as low-performance. Mortality ranged from 5 to 9% in high-performance groups and 10.3–20.9% in low-performance groups. Average daily gain ranged from 0.68–0.86 kg in high-performance groups and 0.63–0.81 kg in low-performance groups. L. intracellularis and PCV2 were detected in most groups, with significant differences in detection rates between high and low-performance groups. Groups with relatively high genomic copies of PCV2 and L. intracellularis that had PRRSV detection presented higher mortality rates (15.75%).DiscussionThis study expanded our understanding of PRRSV, PCV2, and L. intracellularis co-detections and their impact on swine populations.